Representing the Margin and the Center with Interstellar Hassan al-Wazzan in the Heart of Renaissance Italy (London Journal of Research In Humanities and Social Sciences, 2024)
Despite being left out of the limelight of history, Hassan al-Wazzan, a famous Moroccan traveler, figures immensely in Amin Maalouf’s novel, Leo the African. As well as beinghistorically lauded by the pope Leo X as a “man with art and knowledge,” who is moreover “always welcomed among us, not as a servant but as a protector.” The Moroccan globetrotter was thus bestowed with the papal surname, de Medici, as a token of great respect to him. Al-Hassan Ibn Mouhamed al-Wazzan, al-Fasi, had achieved in Europe, as a writer, geographer and papal adviser what many in the same position have not. As he was living in Rome, he wrote in Italian about Islamic culture and the geography of Africa. In the novel of Amin Maalouf Leo the African, we see the writer trying to debunk and dismantle Western stereotyped and prejudiced representations of the other, and then, at a hopefully later stage or during that very gesture, reconstruct in their stead images of the self and the other, images that go beyond the fixity of binary oppositions to celebrate the interdependence and interpretation of same and different
Keywords: accountability; Human Rights; case study; human services; rural social work; access to services; Myanmar; Systemic Functional Linguistics; contrastive study; realizations; transitivity configurations; English; resistance; Al-Wazzan; traveler; captive; adviser; emissary; representation; binary; same; different